Presentation - Bianca Cristina Côrrea; Débora Cristina Piotto; Teise de Oliveira Guaranha Garcia; Elaine Sampaio Araújo; Elmir de Almeida; Marilena Nakano; Marli Pinto Ancassuerd (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
...